So wyou said she was going to
Answer:
Equation: 3y - 6 = y + 7
y = 6.5
Step-by-step explanation:
Step 1: Write out equation
3y - 6 = y + 7
Step 2: Solve for <em>y</em>
2y - 6 = 7
2y = 13
y = 13/2 or 6.5
33square2 i think that is what it is
2x * 3x = 6x^2
2x * (-4) = 8x
7 * 3x = 21x
7 * (-4) = -28
6x^2 + 29x - 28
You would simply have to plug in, or substitute, the given values in the equations.
So, H=-5, W=2 and the problem is 4h-3w
To plug them in, your new equation would be 4(-5)-3(2) and simplify. So it becomes -20-6 which = -26.
And -26 would be your answer.